A Pancancer Study of PIEZO1 as a Prognosis and Immune Biomarker of Human Tumors. (14th June 2022) - Wu, Yunhui; Zhang, Jingying; Hou, Can; Wang, Hongyu; Zhu, Min; Yao, Xin
Abstract : PIEZO1, a mechanosensitive ion channel protein, has been identified in the correlation between several cancers. However, the systematic pancancer study of PIEZO1 still lacks. We examined PIEZO1 across thirty-three types of cancers to explore its role in prognosis and immunological function for the first time. Based on the open databases TCGA, GTEx and CPTAC, PIEZO1 has been demonstrated to be differentially expressed in most cancers compared to adjacent normal tissues. The distinct correlation between PIEZO1 and prognosis of tumor patients was explored by GEPIA2. Genetic alteration of PIEZO1 in the TCGA tumors showed that mutation is the alteration which is linked to OS, DSS, DFS and PFS in some tumors. Alterations of protein phosphorylation levels were detected in some cancers based on the CPTAC dataset. PIEZO1 expression was linked with immune cell infiltration, such as endothelial cell and cancer-associated fibroblast. Finally, KEGG and GO enrichment analyses were applied to investigate the molecular mechanism of PIEZO1. Our first pancancer analysis illustrated the roles of PIEZO1 in different types of tumors.